2018
DOI: 10.1186/s13049-018-0498-x
|View full text |Cite
|
Sign up to set email alerts
|

Simple modification of trauma mechanism alarm criteria published for the TraumaNetwork DGU® may significantly improve overtriage – a cross sectional study

Abstract: BackgroundNo consensus exists in the literature on the use of uniform emergency room trauma team activation criteria (ERTTAC). Today excessive over- or undertriage rates continue to be a challenge for most trauma centres. Application of ERTTAC, published for use in the German TraumaNetwork DGU®, at a Swiss trauma centre resulted in a high overtriage rate. The aim of the investigation was to analyse the ERTTAC in detail with the intention of possible improvement.MethodsThe investigation included consecutive adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
8
0
4
Order By: Relevance
“…Previous studies have shown increases in overtriage rates when efforts were made to decrease undertriage, and similarly, increases in undertriage rates, when attempting to reduce overtriage. [10][11][12][13] The motivation to avoid excessive undertriage could prompt physicians to overtriage to compensate, knowing that the allowable rate for those cases is much greater. Our data, however, indicate that having ISS guidelines at their fingertips allowed the trauma physicians to appropriately triage patients with lower ISS, incidentally improving overtriage rates as well as undertriage rates.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown increases in overtriage rates when efforts were made to decrease undertriage, and similarly, increases in undertriage rates, when attempting to reduce overtriage. [10][11][12][13] The motivation to avoid excessive undertriage could prompt physicians to overtriage to compensate, knowing that the allowable rate for those cases is much greater. Our data, however, indicate that having ISS guidelines at their fingertips allowed the trauma physicians to appropriately triage patients with lower ISS, incidentally improving overtriage rates as well as undertriage rates.…”
Section: Discussionmentioning
confidence: 99%
“…Konsekutive Analyse aller 2018 im SR gemäß standardisierten Kriterien [ 3 ] und/oder infolge eines signifikanten Traumas (New Injury Severity Score, NISS ≥8) [ 15 ] notfallmäßig (innert 24 h) stationär versorgter Verletzten eines Schweizer Zentrumspitals. Die Studie war Teil eines von der zuständigen Ethikkommission (PB_2018-00079 – AG/SO 2012-008) genehmigten Versorgungsforschungsprojektes (NCT02165137).…”
Section: Methodikunclassified
“…We excluded penetrating trauma from this study to homogenize the study population, because it is typically associated with different injuries and treatment regimens, and our cases are few. The decision to use WBCT in individual cases was taken by the trauma leader on duty, which could be seen as a potential confounder, even though internal hospital guidelines recommend its standard use as soon as trauma team activation criteria [17] were actually fulfilled after primary evaluation of the patient in the ER. The evaluation is restricted to the cohort investigated due to its monocenter design and, ultimately, includes more older or less severely injured than several other study groups [29][30][31][32][33].…”
Section: Limitationsmentioning
confidence: 99%